Photo-identification comparison of humpback whale (Megaptera novaeangliae) flukes from Antarctic Area IV with fluke catalogues from East Africa, Western Australia and Eastern Australia - Franklin, Wally; Franklin, Trish; Cerchio, Sal; Rosenbaum, Howard; Jenner, Curt; Jenner, Micheline; Goncalves, Leandra; Leaper, Russell; Harrison, Peter; Brooks, Lyndon; Clapham, Phil (J. Cetacean Res. Manage., 2023)
Early ‘Discovery mark’ data together with recent photo-identification, acoustic, genetic and satellite-radio tag data revealed linkages between humpback whales migrating from breeding grounds (C) off East Africa and the Area III feeding area, from Western Australian breeding grounds (D) and the Antarctic Area IV feeding area and the East Australian breeding grounds (E1) and Antarctic Area V feeding area. These data also revealed low levels of intermingling between (E1) and (D) humpback whales in the Antarctic Area IV feeding area consistent with these being separate populations. Greenpeace photographed the ventral tail flukes of 30 individual humpback whales in the Antarctic Area IV feeding area (70°E–130°E) from 2 to 9 January 2008, between 62°47’S and 64°14’S latitude and 80°00’E and 112°57’E longitude. Comparisons of the Antarctic Area IV Greenpeace fluke catalogue (n = 30) with existing reconciled fluke catalogues from East Africa (n = 842), Western Australia (n = 1,558) and Eastern Australia (n = 1,964), yielded no photo-identification matches. An analysis of the frequencies of whales seen and not seen in Antarctica, East Africa, Western Australia and Eastern Australia relative to the frequencies expected to have been seen and not seen, based on the estimated population sizes and the sizes of the catalogues, provided evidence that the Antarctic whales photographed are from a different population to the East African and East Australian populations. There was weak evidence supporting the hypothesis that the Antarctic whales are from the Western Australian population but insufficient data were available to determine a clear outcome. A comparison of the Antarctic Area IV Greenpeace catalogue (n = 30) with other existing African, Indian Ocean, Western and Eastern Australian and/or Antarctic catalogues, together with increased sampling across the humpback whale feeding season in Antarctica and along the Western and Eastern Australian coastline during their winter migration, is likely to provide further evidence of the migratory destination of these humpback whales. It will also add to our limited knowledge of the extent of population overlap within the Antarctic Area III, IV and V feeding areas.